Adsorption study - dye removal using clay - Sharifah Nhatasha, Syed Jaafar (2006)
The adsorption of textile dyes by clay was investigated using basic dye (Methylene Blue). Adsorption of dye effluent onto clay samples was carried by batch studies at room temperature, 25ºC. The effects of adding clay with zeolite, pH and shaking time towards adsorption performance were investigated. The results from the mixture of 1.0 g clay and 0.01 g zeolite, the increases of pH, pH 9 and the optimum shaking time, 60 min have achieved the maximum dye removal. The adsorption data sucessfully were described by the Langmuir and Freundlich isotherms.